2015
DOI: 10.1016/j.jwpe.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Removal of anionic dyes in aqueous solution by flocculation with cellulose ampholytes

Abstract: a b s t r a c tCellulose ampholytes (CAms) prepared from biocompatible and biodegradable carboxymethyl cellulose (CMC) could represent an environmentally friendly alternative for the efficient removal of anionic dyes from water effluents. In order to evaluate their potential for this application, a series of CAms with a degree of cationic substitution (DS C ) between 0.26 and 1.08 were prepared from sodium CMC, by cationization with 2,3-epoxypropyltrimethylammonium chloride. The flocculation ability of the CAm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…The peak at 2,895 cm -1 is attributed to C-H stretching vibration of the -CH 2 -groups [26]. A series of peaks at 1,162 cm -1 , 1,103 cm -1 , 1,030 cm -1 , 899 cm -1 are attributed to the -COC-group in the cellulose glucose structure [27]. As can be seen from Fig.…”
Section: Ftirmentioning
confidence: 85%
“…The peak at 2,895 cm -1 is attributed to C-H stretching vibration of the -CH 2 -groups [26]. A series of peaks at 1,162 cm -1 , 1,103 cm -1 , 1,030 cm -1 , 899 cm -1 are attributed to the -COC-group in the cellulose glucose structure [27]. As can be seen from Fig.…”
Section: Ftirmentioning
confidence: 85%
“…Langmuir isotherm involves monolayer adsorption on a surface containing homogeneous adsorption sites, without transmigration of adsorbates and without any interaction between the adsorbed molecules (Demirkiran, 2015). Once a site is occupied, no additional adsorption can take place, resulting in saturation of the surface (Kono and Kusumoto, 2015). The Langmuir isotherm is translated by the following relation (Langmuir, 1918) : studies.…”
Section: Adsorptions Isothermsmentioning
confidence: 99%
“…Values obtained in the current study were slightly superior, up to 90%, due to minor differences between xanthan gum and guar gum, and differences in systems behaviors: dyes removal against drinking water treatment. Kono and Kusumoto (2015) investigated the flocculation ability of cellulose ampholytes and observed high color removal at lower concentrations and lower pH values. In this current work, pH was not controlled, but authors also observed that the remaining color (Figure 1) has a tendency to be around the same value, despite the increase in xanthan gum concentration.…”
Section: Coagulation Flocculation and Sedimentation Assaysmentioning
confidence: 99%
“…In practice, synthetic flocculants are employed, such as Poly (diallyldimethyl ammonium chloride (PDADMAC), epichlorohydrin, polyacrylamide (PAM), and its methacrylate analogue is also commercially available, nonetheless they have been associated with health risks due to monomer residues in water (GARCÍA, 2011;GUPTA & AKO, 2005). Nonetheless, previous studies highlighted that natural flocculants could be used, with the advantages of low sensitivity to pH and larger and stronger flocs (KONO & KUSUMOTO, 2015;ZHANG et al, 2013;GARCÍA, 2011;BROSTOW et al, 2009;WEI et al, 2009;WANG et al, 2008;BOLTO & GREGORY, 2007;GUPTA & AKO, 2005).…”
Section: Introductionmentioning
confidence: 99%